Analisis Perilaku Pragmatik dalam Konteks Program Debat Rakyat Bersuara sebagai Model Pembelajaran Pengembangan Keterampilan Berbahasa - Riyanto Riyanto; Ritza Azahara; Achmad Wahidy; Masnunah Masnunah; Aswadi Jaya (Universitas Pendidikan Ganesha, 2025)
The phenomenon of politeness violations in debates often creates communicative tension and reduces the effectiveness of message delivery. This study aims to analyze pragmatic behavior reflected in debate interactions, particularly in relation to adherence to and violations of the principles of politeness. The research focuses on how debate participants comply with or violate politeness maxims in their argumentative exchanges. This study employed a descriptive qualitative approach with data collected through non-participant observation and note-taking, using debate transcripts as the primary source. The subjects were participants actively involved in the debate discourse. The analysis was conducted based on Geoffrey Leech’s theory of politeness, which includes ten politeness maxims. The findings revealed that the agreement maxim (32.6%) and the tact maxim (28.3%) were the most frequently observed, while the most common violations occurred in the approbation maxim (39.5%) and the agreement maxim (32.8%). These results highlight that pragmatic strategies in debates are consciously employed as rhetorical tools to strengthen argumentative positions. The study concludes that debate can be utilized as an instructional model to foster students’ pragmatic competence and politeness in language use, while simultaneously enhancing their critical communication skills.